FAKTOR-FAKTOR YANG MEMPENGARUHI NARAPIDANA REMAJA PUTRA MELAKUKAN SEXUAL HARRASMENT DI LP KELAS II B KOTA PEKANBARU - Erlinawati, Erlinawati; Hasanah, Riza (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
Sexual harassment (sexual harassment) occur due to several contributing factors that exposure to pornography, environment and peer influence. Where a state of their desire to perform sexual harrrasment who supported the state and provoked by the influence of friends at the time. Based on data from the LP Class II B Pekanbaru City in 2013, cases of sexual abuse committed by a group of teenagers category there were 24 people. Whereas in 2014 cases of sexual abuse committed by a group of teenage category, there were 34 people. This illustrates that an increasing number of sexual offenders in the city of Pekanbaru. The purpose of this study was to determine the factors that influence young inmates in doing sexual harrasment at LP II Class B Pekanbaru. This study design was cross-sectional. The population is all young inmates in II Class B LP Pekanbaru City with a total sample of 72 people and the sampling technique with a total sampling. The survey results revealed an association of exposure pornography, environmental and peers with the incidence of sexual harrasment with p value (0.022, 0.008, and 0.019) it explains the correlation of these factors with the incidence of sexual harrasment. It is expected that the prison can cooperate with health workers in providing information about the impact of sexual harrasment, so the inmates related sexual problems harrasment be aware of the fault on all of that and do not want to do sexual harrasment when they were released from prison later